Pelatihan Strategi Pemasaran Melalui Media Online Pada Produk Usaha Rumahan Krupuk Bawang dan Kripik Sukun - Maftuhah, Rifa'atul; Rafsanjani, Haqiqi (Universitas Muhammadiyah Surabaya, 2019)
This journal discusses the marketing training program for home business products of onion crackers and breadfruit chips through online media. The program is very important to do because based on observations in the field the two processed home products still sell their products in conventional ways. The method used in this assistance program is 1) identifying problems, 2) making training programs, 3) making product labels, 4) making product advertisements on online media. The results of the training showed that the participants were very enthusiastic in participating in the program.